Isolation and functional characterization of a cotton ubiquitination-related promoter and 5’UTR that drives high levels of expression in root and flower tissues - Viana, Antonio A. B. (2011)
Background: Cotton (Gossypium spp.) is an important crop worldwide that provides raw material to 40% of the textile fiber industry. Important traits have been studied aiming the development of genetically modified crops including resistance to insect and diseases, and tolerance to drought, cold and herbicide. Therefore, the characterization of promoters and regulatory regions is also important to achieve high gene expression and/or a specific expression pattern. Commonly, genes involved in ubiquitination pathways are highly and differentially expressed. In this study, we analyzed the expression of a cotton ubiquitin-conjugating enzyme (E2) family member with no previous characterization. Results: Nucleotide analysis revealed high identity with cotton E2 homologues. Multiple alignment showed a premature stop codon, which prevents the encoding of the conserved cysteine residue at the E2 active site, and an intron that is spliced in E2 homologues, but not in GhGDRP85. The GhGDRP85 gene is highly expressed in different organs of cotton plants, and has high transcript levels in roots. Its promoter (uceApro2) and the 5’UTR compose a regulatory region named uceA1.7, and were isolated from cotton and studied in Arabidopsis thaliana. uceA1.7 shows strong expression levels, equaling or surpassing the expression levels of CaMV35S. The uceA1.7 regulatory sequence drives GUS expression 7-fold higher in flowers, 2-fold in roots and at similar levels in leaves and stems. GUS expression levels are decreased 7- to 15-fold when its 5’UTR is absent in uceApro2. Conclusions: uceA1.7 is a strong constitutive regulatory sequence composed of a promoter (uceApro2) and its 5’UTR that will be useful in genetic transformation of dicots, having high potential to drive high levels of transgene expression in crops, particularly for traits desirable in flower and root tissues.